Fine Mapping of a Clubroot Resistance Gene in Chinese Cabbage Using SNP Markers Identified from Bulked Segregant RNA Sequencing - Huang, Zhen; Peng, Gary; Liu, Xunjia; Deora, Abhinandan; Falk, Kevin C.; Gossen, Bruce D.; McDonald, Mary R.; Yu, Fengqun (Frontiers in Plant Science, 2017)
Clubroot, caused by Plasmodiophora brassicae, is an important disease of canola (Brassica napus) in western Canada and worldwide. In this study, a clubroot resistance gene (Rcr2) was identified and fine mapped in Chinese cabbage cv. ‘Jazz’ using SNP markers identified from bulked segregant RNA sequencing (BSR-Seq) and molecular markers were developed for use in marker assisted selection. In total, 203.9 million raw reads were generated from one pooled resistant (R) and one pooled susceptible (S) sample, and >173,000 polymorphic single nucleotide polymorphisms (SNP) sites were identified between the R and S samples. One significant peak was observed between 22-26 Mb of chromosome A03, which had been predicted by BSR-Seq to contain the causal gene Rcr2. There were 490 polymorphic SNP sites identified in the region. A segregating population consisting of 675 plants was analysed with 15 SNP sites in the region using the Kompetitive Allele Specific PCR method, and Rcr2 was fine mapped between two SNP markers, SNP_A03_32 and SNP_ A03_67 with 0.1 and 0.3 centi-Morgan from Rcr2, respectively. Five SNP markers co-segregated with Rcr2 in this region. Variants were identified in 14 of 36 genes annotated in the Rcr2 target region. The numbers of poly variants differed among the genes. Four genes encode TIR-NBS-LRR proteins and two of them Bra019410 and Bra019413, had high numbers of polymorphic variants and so are the most likely candidates of Rcr2.